DEVELOPMENT PROSPECTS OF THE PHARMACEUTICAL SECTOR OF THE REPUBLIC OF UZBEKISTAN (Web of Medicine: Journal of Medicine, Practice and Nursing, 2023)
The process of providing the population and preventive treatment institutions with high-quality and effective drugs and medical supplies is directly related to the material and technical base of pharmacy institutions and its technical condition. Also, supply of basic tools at the level of demand plays a special role in increasing the profitability of the pharmacy. In this work, the main tools were analyzed on the example of JSC "Dori-Darmon" of the Tashkent region. In the results of the analysis, the technical condition of the main tools was evaluated, serviceability, wear coefficients were determined, and the efficiency of use was calculated based on general indicators. Based on the analysis, recommendations aimed at increasing the efficiency of the use of the main means of the pharmacy were developed.